PENGARUH PERSPEKTIF FRAUD TRIANGLE TERHADAP KECURANGAN LAPORAN KEUANGAN - Fauziati, Popi; Hamdi, Mukhlizul; Karimi, Kasman; Rahmawati, Novia; Husna, Nailal (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to determine the effect of financial stability, external pressure, financial targets, nature of industry, and rationalization on fraudulent financial statements. The population in this study were primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) and this sample consisted of 47 companies that fit the research criteria. The data used is the company's annual report obtained from the official website of the indonesia stock exchange, company websites and other sources. The data analysis method used is logistic regression using SPSS version 25. The results of the determination test show that the independent variables have a dependent effect of 36%. The results of hypothesis testing show that financial stability has an effect on fraudulent financial reporting and external pressure, financial targets, and rationalization have a positive effect on firm value. Meanwhile, the nature of industry has no significant effect on fraudulent financial statements.Key words: Financial Stability, External Pressure, Financial Targets, Nature Of Industry, Rationalization, Fraudulent Financial Statements